VPS13 and bridge-like lipid transporters, mechanisms, and mysteries - Swan, Laura Elizabeth (Frontiers in Neuroscience, 2025)
Bridge-like lipid transporters (BLTPs) have recently been revealed as key regulators of intraorganellar lipid trafficking, with their loss being associated with defective synaptic signalling and congenital neurological diseases. This group consists of five protein subfamilies [BLTP1-3, autophagy-related 2 (ATG2), and vacuolar protein sorting 13 (VPS13)], which mediate minimally selective lipid transfer between cellular membranes. Deceptively simple in both structure and presumed function, this review addresses open questions as to how bridge-like transporters work, the functional consequences of bulk lipid transfer on cellular signalling, and summarises some recent studies that have shed light on the surprising level of regulation and specificity found in this family of transporters.